ANALISIS PENGARUH PENDAPATAN USAHA, PERPUTARAN PERSEDIAAN, BEBAN OPERASIONAL TERHADAP LABA BERSIH PADA SEKTOR CONSUMER CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023 - Adhani, Ida; Fitri Rahmawati, Dea (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
The purpose of this research is to determine the analysis of the influence of business income, inventory turnover, operational expenses on net profit in the consumer cyclical sector listed on the Indonesian Stock Exchange (BEI) in 2020-2023. The type of data is secondary data from the financial reports of consumer cyclical sector companies listed on Indonesian Stock Exchange for the 2020-2023 period. Sampling was carried out by purposive sampling. The analysis techniques used are the Classical Assumption Test, Descriptive Statistics, Multiple Linear Regression, Coefficient of Determination (R2), t Test and F Test. The results of this study show that partial business income has no and significant effect on net profit, partial inventory turnover has an influence positive and significant on net profit and operational expenses partially have a significant influence on net profit. The results are simultaneously known as Business Income, Operational Costs, Inventory Turnover to Net Profit. The predictive ability of the three independent variables on Net Profit can be seen from the Adjust R Square value of 40.2%, while the remaining 59.8% is influenced by other variables outside the research variables.